Bulky hinge bracelet / Muhammad Zairulhakeem Mohd Zainuddin - Mohd Zainuddin, Muhammad Zairulhakeem (2022)
Jewelery set inspired by Malaysian culture and motif batik sarung was chosen as the subject matter. Already used by our old generation until now. Contemporary as the concept of design, shape and the artistic curve line on Keris ware transform into Jewellry design through ideation and development of idea.